Validity and Practicality of Media Using Digital Pop-Up Books in Pancasila Education Learning in Elementary Schools - Yelmiwati , Sella; Reinita, Reinita; Waldi, Atri; Amsari , Dina (FKIP - Universitas Riau, 2025)
This research is motivated by the low use of technology-based learning media in several elementary schools located in Lima Puluh Kota Regency. The technology-based learning media used by teachers is limited to showing images and videos from YouTube. This research aims to develop a valid, and practical digital pop-up book learning for fourth-grade elementary school students. The type of research used is Research and Development with the ADDIE model. The research instruments and data analysis carried out are: 1) validity in the form of product assessment instruments by experts in such subject matter, language, and media; and 2) practicality in the form of teacher and student response questionnaires. The research results show a content validity score of 96%, language validation results of 86%, and media validation results of 96%. In the implementation showed that the digital pop-up book learning media used in the learning process was very practical. Therefore, it can be concluded that this digital pop-up book learning media is very suitable for use in elementary schools.